Circadian rhythms-related disorders in diurnal fat sand rats under modern lifestyle conditions: A review - Bilu, Carmel; Einat, Haim; Zimmet, Paul; Kronfeld-Schor, Noga (Frontiers in Physiology, 2022)
Modern lifestyle reduces environmental rhythmicity and may lead to circadian desynchrony. We are exposed to poor day-time lighting indoors and excessive night-time artificial light. We use air-conditioning to reduce ambient temperature cycle, and food is available at all times. These disruptions of daily rhythms may lead to type 2 diabetes mellitus (T2DM), obesity, cardiometabolic diseases (CMD), depression and anxiety, all of which impose major public health and economic burden on societies. Therefore, we need appropriate animal models to gain better understanding of their etiologic mechanisms, prevention, and management. We argue that the fat sand rat (Psammomys obesus), a diurnal animal model, is most suitable for studying the effects of modern-life conditions. Numerous attributes make it an excellent model to study human health disorders including T2DM, CMD, depression and anxiety. Here we review a comprehensive series of studies, utilizing the fat sand rat to study the underlying interactions between biological rhythms and health. Understanding these interactions will help deciphering the biological basis of these diseases, which often occur concurrently. We found that when kept in the laboratory (compared with natural and semi-wild outdoors conditions), fat sand rats show low amplitude, nocturnal or arrhythmic activity patterns, dampened daily glucose rhythm, glucose intolerance, obesity and decreased survival rates. Short photoperiod acclimation exacerbates these pathologies and further dampens behavioral and molecular daily rhythms, resulting in CMD, T2DM, obesity, adipocyte dysfunction, cataracts, depression and anxiety. Increasing environmental rhythmicity by morning bright light exposure or by access to running wheels strengthens daily rhythms, and results in higher peak-to-trough difference in activity, better rhythmicity in clock genes expression, lower blood glucose and insulin levels, improved glucose tolerance, lower body and heart weight, and lower anxiety and depression. In summary, we have demonstrated that fat sand rats living under the correspondent of “human modern lifestyle” conditions exhibit dampened behavioral and biological rhythms and develop circadian desynchrony, which leads to what we have named "The Circadian Syndrome". Environmental manipulations that increase rhythmicity result in improvement or prevention of these pathologies. Similar interventions in human subjects could have the same positive results and further research on this should be undertaken.